PENGARUH PREHEAT DAN THERMAL TENSIONING TERHADAP KUALITAS SAMBUNGAN LAS TIG Al 6061-T6 - Yunaidi Yunaidi (JURNAL FOUNDRY, 2013)
Aluminum 6061-T6 is one the aluminum alloys which is widely used in engineering practice, such as automotive industry, piping, tanks, aircraft and shipping, because of many advantages including light weight, high tensile strength, corrosion resistant, able to shape and good weldability. Welding process is widely used today. The problem often encountered when using a welding method is the low strength of welded joints compared with the parent metal and the presence of distortion, especially for thin materials, due to residual stresses that arise during welding process. High tensile residual stress in welded joints can lead to brittle fracture, stress corrosion cracking, and accelerate the propagation rate of fatigue. This study aims to determine the effect of preheat, static thermal tensioning (STT), and transient thermal tensioning (TTT) on the quality of welding as indicated by the test of micro structure, hardness test, and tensile test of TIG welded joints of Al 6061-T6.The results showed that the preheat, STT, and TTT can change the size and shape of grains in the weld area and HAZ regions. Preheat, STT, and TTT can increase the tensile strength and yield stress in the weld area. The highest tensile strength occurs in the STT that is equal to 194 MPa, or increase by 43.5% compared to the tensile strength of the weld without treatment. The highest yield stress also occurs in the STT that is equal to 154 MPa, or increase by 104.4% compared to the yield stress in the weld without treatment.